Effectiveness of SYTOX Green Stain for Bacterial Viability Assessment - Lebaron, P. (American Society for Microbiology, 1998)
The effectiveness of SYTOX Green nucleic acid stain for measuring bacterial viability was tested on starved populations of Escherichia coli and Salmonella typhimurium. This stain underestimates the fraction of dead cells within starved populations containing cells with damaged nucleic acids or membranes. Its application to natural samples should be considered with caution.